Spiders or Butterflies? Despite Student Preference, Gender-Biased Lesson Models. Do Not Impact Interest, Attitude, and Learning in Biology - Buxton, Amy; Jensen, Jamie; Wright, Geoff; Bybee, Seth; Phillips, Andrea; Phillips, Tanner; Steadman, Michael (Advances in Social Sciences Research Journal, 2020)
Background: Educational research often emphasizes the prevalent gender gap between males and females in science, technology, engineering, and mathematics (STEM) fields. In our study, we took a new approach on gender research by specifically considering whether there is a gender-oriented preference in curricular models (the specific lesson examples and content used to teach a broader biology topic, e.g., dust mites as a model of symbiosis) implemented to teach biology and how these models affect student interest, attitude, and learning. We sampled kindergarten through sixth grade students to determine whether a gender-oriented preference concerning lesson models exists and when that preference is most prevalent. We then designed active-learning curricula surrounding the models showing the largest gender preference and measured whether lesson model or presenter gender impacted student interest, attitude, and learning. Results: Our findings show that students do indeed indicate a preference to learn using their own gender-oriented lesson models from kindergarten through sixth grade, but that the lesson model and presenter gender do not impact student interest, attitude, or learning during an active learning biology presentation. Conclusions: Our findings suggest that teachers as early as kindergarten should be aware and sensitive to the gender-based preferences for models used in teaching science that may exist within their classrooms and opt to alternate between male- and female-oriented lesson models to create a more inclusive classroom and to encourage especially females to pursue science. However, we offer strong advice to teachers to implement active-learning lessons as this may be the key to eliminating such gendered effects, as shown by our research.